EFFECTS OF SLEEP DISORDERS ON STUDENTS' COGNITIVE ABILITIES - Boymurodova Nazokat Chori qizi; Asqarova Iroda Baxtiyor qizi; Qosimova Hadicha Jahongir qizi (Bright Mind Publishing, 2025)
A statistical analysis was conducted to study the impact of sleep disorders on cognitive function among students. Sleep is undoubtedly one of the most important physiological activities for the proper and normal functioning of the human body.Insufficient sleep has a negative impact on cardiovascular diseases, neurocognitive function, psychological disorders, metabolic abnormalities, and academic performance. Cognitive function is memory, mental activity, and other cognitive functions. The article examined the impact of sleep deprivation on cognitive function among medical students. According to the results, it was found that sleep disorders have a negative impact on students' cognitive function.
Keywords: Cognitive function, sleep disorder, student, cognitive function, academic performance, mental activity, memory.